ANALISIS KEANDALAN PADA PENYULANG ARJUNA DENGAN TERPASANGNYA RECLOSER DOUBLE SIX MENGGUNAKAN METODE SECTION TECHNIQUE - Adi Wicaksana, I Ketut; Rinas, I Wayan; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2018.v05.i01.p08, 2018)
Penyulang Arjuna is a medium voltage Network in supply from GI Pemecutan Kelod power with a capacity of 60 MVA, and channel length 10,202 km. Before mounted Recloser Double Six, the Reliability Index Penyulang Arjuna 0,4001 SAIFI value times/ customer/year, and the value of SAIDI 3,9355 hours/customers/year. Penyulang Arjuna never had 10 times the trip in the year 2015, thus affecting the level of reliability. To tackle these problems, in doing the installation of Recloser Double Six. Reliability analysis using the method of Section Technique. The results of the analysis after the installation of the Recloser Double Six is the value of SAIFI 0,2240 times/customer/year, and the value of SAIDI 2,0714 hours/ customers/year. With the declining value of SAIFI and SAIDI after mounting the Recloser Double Six, increased reliability and meet the standards of reliability index SAIFI of 3,2 times/year and SAIDI, amounting to 21 hours/year corresponding SPLN No. 68-2 years 1986.